2020
DOI: 10.4274/tjod.galenos.2019.09476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation inflammatory markers of hemogram parameters in primary ovarian insufficiency

Abstract: Pek çok primer ovaryen yetersizlik (POI) olgusunda yeterli etiyolojik değerlendirme yapılmamaktadır. Mevcut çalışmalar POI etyopatogenezinde enflamatuvar belirteçlerin rolü ololduğunu göstermiştir. Bu çalışmanın amacı POI hastalarında hemogram parametrelerindeki enflamatuvar belirteçlerinin rolünü araştırmaktır. Gereç ve Yöntemler: Çalışmada 47 sağlıklı kadın ile 47 POI hastası kadının hastane kayıtları retrospektiif olarak karşılaştırılmıştır. Hemogram, ve 3. gün bakılan hormon profilleri değerlendirilmiştir.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Hemogram parameters, on the other hand, provide information regarding human health. Several studies showed the importance of hemogram parameters as predictors or indicators of dementia [ 5 ], primary ovarian insufficiency [ 6 ] and type 2 diabetes mellitus [ 3 ]. However, few studies have investigated the association between heavy metal pollution and hemogram parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hemogram parameters, on the other hand, provide information regarding human health. Several studies showed the importance of hemogram parameters as predictors or indicators of dementia [ 5 ], primary ovarian insufficiency [ 6 ] and type 2 diabetes mellitus [ 3 ]. However, few studies have investigated the association between heavy metal pollution and hemogram parameters.…”
Section: Introductionmentioning
confidence: 99%
“…31).Ovarian aging causes a decline in estrogen production and an increase in inflammatory mediators. Thus, the ovarian reserve is diminished, and the number of inflammatory cells increases.…”
mentioning
confidence: 99%